Reply to the "Comment by Delmelle et al. (2013) on 'Scavenging of sulfur, halogens and trace metals by volcanic ash: The 2010 Eyjafjallajökull eruption' by Bagnato et al. (2013)" - Bagnato, E.; Aiuppa, A.; Bertagnini, A.; Bonadonna, Costanza; Cioni, R.; Pistolesi, M.; Pedone, M.; Hoskuldsson, A. (Geochimica et Cosmochimica Acta, 2014)
With this short communication we address the principal issues raised by Delmelle et al. (2014) in relation to the work of Bagnato et al. (2013) concerning the 2010 eruption of Eyjafjallajökull, Iceland. The principal conclusions of the work of Bagnato et al. (2013) include the observation that protracted gas-aerosol interaction in the plume promotes selective leaching of cation species from ash, with alkalis and Ca (and, among trace elements, Zn and Cu) being more rapidly re-mobilized (and transferred to soluble surface salts) relative to more inert elements (Mg, Ti). They also observed that adsorption onto ash surfaces is a major atmospheric sink of volcanic acidic gases, with 282 tons of elemental sulfur and 605–691 tons of halogens being daily ground deposited via ash over Iceland in early May 2010. Acidic gas adsorption onto ash increases almost linearly with plume aging (e.g., upon increasing in-plume residence times of ash and gases), and is seen to proceed at about 3 time faster rates for HF than for SO2 and HCl. However, Delmelle et al. (2014) criticized our strategies for data acquisition, processing and interpretation. They also raised some objections concerning several key topics explored by Bagnato et al. (2013), with a special focus on the discussion of rates of interaction between ash particles and gases in a volcanic cloud, and the consequent formation of soluble salts on ash surfaces. They also considered incorrect the estimate of depositional fluxes and volatile budget for the Eyjafjallajökull eruption. While we appreciate the in-depth analysis of Delmelle et al. (2014), we show that most of their criticisms derive from a partial and sometimes incorrect understanding of the work of Bagnato et al. (2013), which overall led to unsupported conclusions and misleading analysis of the original results. Here, we present a detailed response to the comments of Delmelle et al. (2014), accompanied by additional explicative material. The principal conclusions presented in Bagnato et al. (2013) are given ...